ICT IN HIGHER EDUCATION - Buttar, Sandeep Singh (PEOPLE: International Journal of Social Sciences, 2016)
Since time immemorial, education has been an important instrument for social and economic transformation. Presently higher education in India is experiencing a major transformation in terms of access, equity and quality. This transition is highly influenced by the swift developments in information and communication technologies (ICTs) all over the world. The introduction of ICTs in the higher education has profound implications for the whole education process especially in dealing with key issues of access, equity, management, efficiency, pedagogy and quality. At the same time the optimal utilization of opportunities arising due to diffusion of ICTs in higher education system presents a profound challenge for higher educational institutions. In this backdrop, the paper addresses the opportunities and challenges posed by integration of ICTs in various aspects of higher education in the present scenario.